Intertextuality and Scapegoating Motif in Yoruba Myth of Ayélála and Judeo-Christian Narrative of Jesus - Oyetimi, Kehinde (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
Myths have always been significant parts of the oral traditions of preliterate societies. As the creative repository of indigenous communities, myths express the shared ecosystem of communal ideologies and cultural identities. As vital narratives, myths—whether in their symbolical, literal or allegorical multimodalities—are artistically constructed to serve cosmological and ontological purposes. Given their very universal appeal and representation, myths frequently exhibit cross-cultural correspondences, borrowing motifs, themes, and characters from remote, neighboring or dominant cultures. Intertextuality, the weaving together of diverse cultural elements within myths, suggests that texts are part of a larger network influencing and shaping one another, fostering dialogue and meaning production through interaction. It encompasses practices like ritual performances, quotation, allusion, parody, pastiche, and adaptation, encouraging readers to be active participants in uncovering hidden layers of meaning. Earlier studies on ritual practices for restoring social order and cosmic balance have established the criticality of the scapegoat motif. While engaging intertextuality and social drama as theoretical framework, this study examined layers of cross-cultural parallels of the scapegoat motif in the Yoruba myth of Ayélála and the Judeo-Christian narrative of Jesus. In both myths, the scapegoat emerges as a character or entity burdened with blame or punishment for the sins or troubles of others, often sacrificed to restore communal harmony or absolve guilt.